2014
DOI: 10.1089/scd.2013.0390
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Human Menstrual Blood Progenitor Cells Improves Hyperglycemia by Promoting Endogenous Progenitor Differentiation in Type 1 Diabetic Mice

Abstract: Recently, a unique population of progenitor cells was isolated from human menstrual blood. The human menstrual blood progenitor cells (MBPCs) possess many advantages, such as the noninvasive acquisition procedure, broad multipotency, a higher proliferative rate, and low immunogenicity, and have attracted extensive attention in regenerative medicine. Preclinical studies to test the safety and efficacy of MBPCs have been underway in several animal models. However, relevant studies in type 1 diabetes mellitus (T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 52 publications
0
101
0
2
Order By: Relevance
“…MSCs have been shown the tropic properties towards damaged tissues38 and tumor microenvironment39, which improve the efficiency and target ability of MSC-based therapy. We and other groups have reported the potential application of EnSCs to restore function of injured tissues91238.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs have been shown the tropic properties towards damaged tissues38 and tumor microenvironment39, which improve the efficiency and target ability of MSC-based therapy. We and other groups have reported the potential application of EnSCs to restore function of injured tissues91238.…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have reported the potential application of EnSCs to restore function of injured tissues91238. However, there are some concerns about the potential risk of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MenSCs were isolated and provided by the State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, First Affiliated Hospital, School of Medicine, Zhejiang University (Mou et al 2013, Wu et al 2014, Lai et al 2015. Briefly, human menstrual blood was collected The χ 2 test was applied.…”
Section: Menscs Culture and Labelingmentioning
confidence: 99%
“…MenSCs exhibit higher proliferation rates than bone marrow-derived MSCs and can be easily obtained without invasive procedures [911]. In particular, our and other groups have reported that MenSCs induce low-level immunogenicity in clinical studies and can be expanded through at least 20 passages without genetic abnormalities [9, 12, 13]. The therapeutic potential of MenSCs has been demonstrated in several disease models, such as Duchenne muscular dystrophy, stroke, type 1 diabetes, premature ovarian failure, and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%